Analysis of the physicochemical properties of calcium silicate based cements used in retrograde and endodontic fillings - Silva, Ericke Mucke (2021)
Objective 1: To evaluate volumetric change, pH, calcium release and radiopacity of calcium silicate repair cements: Endosequence RRM, Bio C Repair, MTA REPAIR HP, Ortho MTA, Ortho MTA plus 5% calcium oxide. Objective 2: Evaluate volumetric change, pH, calcium release, radiopacity and flow of three ready-to-use calcium silicate-based endodontic sealers: Endosequence BC Sealer, Bio C Sealer and Sealer Plus BC. Methodology: For repair cements, fifty acrylic teeth had their retro cavities filled with cements accordingly with the groups (n=10). The teeth were fixed in a plastic container and the apexes were kept in 10 mL of ultrapure water. Then, a Micro-CT 1174 scanning was performed to evaluate the volumetric change of the materials. The images were reconstructed, and the volume change of the materials was measured. The pH level and calcium ions release were evaluated using the ultrapure water of the plastic container in 3, 24, 72, and 168h. For radiopacity analysis, 3 specimens of each cements were placed on occlusal films together with an aluminum scale. The radiographs were digitalized and the radiographic density was assessed. Data were statistically analyzed by the ANOVA, Tukey, Kruskal-Wallis, and Dunn tests. For the sealers tests, root canals of thirty prototypes of upper incisor acrylic teeth were filled with sealer and gutta percha point, then immersed in containers with 13 ml of ultrapure water following the same methodology as the repair materials, including the flow test for this group of materials. Results 1: MTA Repair HP and Bio C Repair respectively presented the lowest and the highest volumetric change, (P<0.05). Endosequence RRM presented the highest radiopacity (P<0.05). All materials presented calcium release and alkalinization capacity. Results 2: Endosequence BC Sealer presented the lowest, and Bio C Sealer the highest volumetric change after 72 and 168h (p<0.05). Endosequence BC Sealer presented higher radiopacity (p<0.05). All materials showed alkalinization capacity. Conclusions: Among repair materials, Bio C Repair showed the highest volumetric change values, while MTA Repair HP the lowest values among them. All materials presented calcium release and alkalinization capacity, also their radiopacity values were above the minimum required by the ISO standard. Regarding the sealers. All materials presented alkalinization, calcium release capacity, radiopacity and flow values above the minimum required by the ISO standard. Bio C Sealer showed the highest volumetric loss, while Endosequence BC Sealer was the one that lost the least volumetrically.